Pengaruh Penggunaan Bahasa Gaul Terhadap Kemampuan Berbahasa Indonesia Pada Generasi-Z - Ningrum Cahayu; Leonny Raicella Sumbayak; Wisman Hadi (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
. This research aims to find out how slang affects Generation-Z's Indonesian language skills. This research uses a natural research design, which means the researcher looks at the phenomenon directly rather than changing the research design. In addition, researchers collected data through online questionnaires. Research on the influence of the use of slang on the Indonesian language skills of the younger generation shows that there is a significant impact of the use of slang on their Indonesian language skills. Frequent use of slang can affect grammar, vocabulary and sentence structure skills in Indonesian. The younger generation who often use slang tends to show a decline in their ability to write and speak good and correct Indonesian.